The impact of foreign direct investment on local economic growth in Vietnam: A case study of Thai Nguyen province (1993-2024) - Tuan, Nguyen Minh (Edelweiss Applied Science and Technology, 2026)
This research examines the relationship between foreign direct investment (FDI) and local economic growth in Thai Nguyen Province, Vietnam, during the period 1993-2024. Using a case study approach and descriptive statistical analysis based on secondary data, the research reviews realized FDI capital, FDI structure by investment partner and economic sector, and GRDP growth in the province over time. The findings show that FDI has played an important role in expanding social investment, accelerating industrialization, restructuring the local economy, promoting exports, and supporting employment creation. The most visible turning point occurred after 2013, when large-scale investment by Samsung and related supporting firms significantly increased FDI inflows and industrial output. However, the results also indicate that fluctuations in FDI growth were much stronger than fluctuations in GRDP growth, suggesting that the contribution of FDI to economic growth, while positive, was uneven and its spillover effects remained limited. The research provides empirical evidence from a long-term provincial case and offers policy implications for improving the quality, efficiency, and sustainability of FDI attraction in Vietnam.